2011
DOI: 10.3201/eid1710.110349
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium knowlesiMalaria in Humans and Macaques, Thailand

Abstract: This parasite may be transmitted from macaques to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 32 publications
1
116
0
3
Order By: Relevance
“…Because the initial blood smears of the patient contained various stages of malaria with unusually high parasite density, nested polymerase chain reaction analyses targeting the 18S rRNA and the mitochondrial cytochrome b genes of human malaria species were performed as previously described. 4,5 Results of these assays confirmed that the patient was infected with P. knowlesi.…”
Section: Case Reportsupporting
confidence: 50%
See 2 more Smart Citations
“…Because the initial blood smears of the patient contained various stages of malaria with unusually high parasite density, nested polymerase chain reaction analyses targeting the 18S rRNA and the mitochondrial cytochrome b genes of human malaria species were performed as previously described. 4,5 Results of these assays confirmed that the patient was infected with P. knowlesi.…”
Section: Case Reportsupporting
confidence: 50%
“…It is noteworthy that all these knowlesi malaria patients, either having monoor mixed species infections, had uncomplicated symptoms and were responsive to chloroquine and a combination of artesunate and mefloquine. [4][5][6] Herein, we describe severe manifestations of knowlesi malaria in a newly recognized Thai patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these reports suggest that P. knowlesi infections in humans are wide spread in South-east Asia. Retrospective analysis of malaria cases identified by microscopy more than 10-12 years back in Malaysian Borneo ( (Lee et al 2009b) and Tak province in Thailand (Jongwutiwes et al 2011) found P. knowlesi infections among them. These studies suggest that P. knowlesi is not a new emergent simian malaria parasite in humans, and it was present in humans prior to Singh et al (2004) report.…”
Section: Natural P Knowlesi Infections In Humansmentioning
confidence: 99%
“…Plasmodium vivax has been described as the benign form of malaria, yet many case reports showed that vivax malaria remains responsible for severe clinical manifestations and mortality in vivax-endemic areas (4). Knowlesi-infection is widely distributed in South East Asian countries (5)(6)(7)(8)(9) and could lead to hyperparasitemia in a short period as P. knowlesi has the fastest life cycle of 24 hours among the human Plasmodium sp. (10).…”
Section: Introductionmentioning
confidence: 99%